Indoor radon survey in Visegrad countries - Műllerová, Monika; Kozak, Krzysztof; Kovács, Tibor; Smetanová, Iveta; Csordás, Anita; Grzadziel, Dominik; Holý, Karol; Mazur, Jadwiga; Moravcsík, Attila; Neznal, Martin; Neznal, Matej (Applied radiation and isotopes, 2016)
The indoor radon measurements were carried out in 123 residential buildings and 33 schools in Visegrad countries (Slovakia, Hungary and Poland). In 13.2% of rooms radon concentration exceeded 300Bqm(-3), the reference value recommended in the Council Directive 2013/59/EURATOM. Indoor radon in houses shows the typical radon behavior, with a minimum in the summer and a maximum in the winter season, whereas in 32% of schools the maximum indoor radon was reached in the summer months.
Keywords: průzkumy a dotazníky; Air Pollutants, Radioactive; Poland; Polsko; Humans; radon; Seasons; Maďarsko; Housing; Surveys and Questionnaires; znečištění vzduchu ve vnitřním prostředí; Slovenská republika; Slovakia; radioaktivní látky znečišťující vzduch; školy; Hungary; lidé; bydlení; Schools; roční období; Radon; Air Pollution, Indoor